(untitled) (Experimental biology, 2026)
This article presents the results of a comprehensive assessment of the ecological status of populations of the rare endemic species Schmalhausenia nidulans native to the high-mountain regions of the Northern Tien Shan. The aim of the study was to investigate the current state of the species populations by analyzing their numbers, ontogenetic structure, morphometric parameters, and anatomical features. Two natural populations of the species were examined: the first population, located on the Uzynkara Ridge at an altitude of 3003 m above sea level, and the second population, growing on the Ile-Alatau Ridge at an altitude of 3260 m above sea level. During the field research, the population size, age structure, and morphological traits of individuals at the juvenile, immature, virginal, and generative stages of development were studied, and an anatomical analysis of the stem structure was also conducted.